Effect of Profitability, Dividend Policy, Free Cash Flow, and Market Capitalization on Bank Firm Value - Gracelin Nonifati Hulu; Abdillah Arif Nasution; Rina Br. Bukit (Harmoni Economics: International Journal of Economics and Accounting, 2026)
Firm value is a crucial indicator of market perception of a company’s performance and long-term sustainability, particularly in the banking sector, which plays a strategic role in the Indonesian economy. However, inconsistencies in empirical findings regarding the determinants of firm value indicate the need for further investigation. This research aims to analyze the effect of profitability, dividend policy, free cash flow, and market capitalization on firm value, as well as to examine the moderating role of Good Corporate Governance (GCG) in banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. This study employs a quantitative research approach using panel data regression analysis and Moderated Regression Analysis (MRA), processed with EViews 12 software. The research sample consists of 13 banking companies selected through purposive sampling, resulting in 52 firm-year observations. The results indicate that profitability and market capitalization have a positive and significant effect on firm value, while dividend policy and free cash flow do not significantly influence firm value. Furthermore, the moderation analysis reveals that only the independent commissioner variable is able to strengthen the relationship between profitability and firm value, whereas GCG self-assessment does not moderate any of the examined relationships. These findings suggest that investors place greater emphasis on fundamental financial performance indicators and the effectiveness of independent commissioners as an internal governance mechanism in enhancing firm value. In conclusion, strengthening profitability performance and optimizing the role of independent commissioners are essential strategies for increasing firm value in the banking sector.